Major histocompatibility complex (MHC) class II alleles, haplotypes and epitopes which confer susceptibility or protection in systemic sclerosis: analyses in 1300 Caucasian, African-American and Hispanic cases and 1000 controls. Issue 5 (12th July 2009) - Arnett, Frank C; Gourh, Pravitt; Shete, Sanjay; Ahn, Chul W; Honey, Robert E; Agarwal, Sandeep K; Tan, Filemon K; McNearney, Terry; Fischbach, Michael; Fritzler, Marvin J; Mayes, Maureen D; Reveille, John D
Abstract : Objective: To determine human leucocyte antigen-class II (HLA-class II) (DRB1, DQB1, DQA1 and DPB1) alleles, haplotypes and shared epitopes associated with scleroderma (systemic sclerosis (SSc)) and its subphenotypes in a large multi-ethnic US cohort by a case–control association study. Patients and methods: 1300 SSc cases (961 white, 178 black and 161 Hispanic subjects) characterised for clinical skin forms (limited vs diffuse), SSc-specific autoantibodies (anticentromere (ACA), anti-topoisomerase I (ATA), anti-RNA polymerase III (ARA), anti-U3 ribonucleoprotein (fibrillarin)) and others were studied using molecular genotyping. Statistical analyses in SSc itself by ethnicity, gender, skin type and autoantibodies were performed using exact logistic regression modelling for dominant, additive and recessive effects from HLA. Results: The strongest positive class II associations with SSc in white and Hispanic subjects were the DRB1*1104, DQA1*0501, DQB1*0301 haplotype and DQB1 alleles encoding a non-leucine residue at position 26 ( DQB1 26 epi), while the DRB1*0701, DQA1*0201, DQB1*0202 haplotype and DRB1*1501 haplotype were negatively correlated and possibly protective in dominant and recessive models, respectively. These associations did not discriminate between limited and diffuse SSc. SSc in black subjects was associated with DRB1*0804, DQA1*0501, DQB1*0301 alleles. DPB1*1301 showed the highest odds ratio for ATA (OR = 14). Moreover, it showed no linkage disequilibrium or gene interaction with DR/DQ. ACA was best explained by DQB1*0501 and DQB1*26 epi alleles and ARA by DRB1*0404, DRB1*11 and DQB1*03 alleles in white and Hispanic subjects but DRB1*08 in black subjects. Conclusion: These data indicate unique and multiple HLA-class II effects in SSc, especially on autoantibody markers of different subphenotypes.